2004
DOI: 10.1074/jbc.m405045200
|View full text |Cite
|
Sign up to set email alerts
|

Jak2 Tyrosine Kinase Mediates Oxidative Stress-induced Apoptosis in Vascular Smooth Muscle Cells

Abstract: In vascular smooth muscle cells, Jak2 tyrosine kinase becomes activated in response to oxidative stress in the form of hydrogen peroxide. Although it has been postulated that hydrogen peroxide-induced Jak2 activation promotes cell survival, this has never been tested. We therefore examined the role that Jak2 plays in vascular smooth muscle cell apoptosis following hydrogen peroxide treatment. Here, we report that Jak2 tyrosine kinase activation by hydrogen peroxide is required for apoptosis of vascular smooth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 24 publications
5
31
0
1
Order By: Relevance
“…Treatment with the JAK2 inhibitor AG490 (ref. 39) or the STAT5 inhibitor nicotinoyl hydrazone 40 led to upregulation of MSI1 in the oncospheres ( Fig. 5b,c ).…”
Section: Resultsmentioning
confidence: 89%
“…Treatment with the JAK2 inhibitor AG490 (ref. 39) or the STAT5 inhibitor nicotinoyl hydrazone 40 led to upregulation of MSI1 in the oncospheres ( Fig. 5b,c ).…”
Section: Resultsmentioning
confidence: 89%
“…Interestingly, several studies have reported cross talk between the insulin receptor kinase and the Janus-activated kinase (JAK) signaling pathways [56-58]. In particular, JAK2 - the major mediator of inflammatory cytokine signaling in mammalian cells - can be activated by hydrogen peroxide [59] and contributes to insulin-dependent activation of p38 MAPK, JNK, and ERK in a manner that is independent of insulin receptor substrate activation and activation of the phosphatidylinositol 3-kinase/Akt-dependent arm of insulin signaling [60]. Jaramillo-Gutierrez et al .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is increasingly implicated in the development of atherosclerosis (5) and increased oxidative damage, and elevated levels of DNA strand breaks occur in human atherosclerotic plaques (6). Oxidative stress reduces IGF1R expression and induces VSMC apoptosis in culture (7)(8)(9)(10). Reduced IGF1R expression is also seen within plaques, suggesting that IGF1R-dependent survival regulates apoptosis in vivo (11,12).…”
mentioning
confidence: 99%